The Importance of the Microbiota in Cervical Cancer Pathogenesis and Therapy - Krzyśkowska, Sylwia; Krukowska, Kamila; Kulczykowska, Wiktoria; Kozińska, Anna; Krupa, Martyna; Krawiec, Laura; Paszt, Zuzanna (Quality in Sport, 2026)
Background. Cervical cancer remains a significant public health challenge despite advances in screening and HPV vaccination. Persistent infection with oncogenic human papillomavirus (HPV) is the primary etiological factor; however, additional components of the cervical microenvironment, including the cervicovaginal microbiota, may influence disease development. Aim. This review aims to summarize current knowledge on the role of the cervicovaginal microbiota in cervical cancer pathogenesis and its potential clinical relevance in diagnosis, prognosis, and treatment. Material and methods. A narrative review of the literature was conducted, focusing on studies investigating the composition, function, and clinical significance of the cervicovaginal microbiota in relation to HPV infection and cervical cancer. Results. Under physiological conditions, the vaginal microbiota is dominated by Lactobacillus species, which maintain an acidic environment and provide protection against pathogenic microorganisms. Dysbiosis, characterized by reduced Lactobacillus abundance and increased microbial diversity, is associated with HPV persistence, chronic inflammation, and progression of precancerous lesions. Certain microorganisms, including Lactobacillus iners, may be associated with poorer treatment outcomes and resistance to chemoradiotherapy. Moreover, specific microbiota profiles may serve as potential diagnostic and prognostic biomarkers. Conclusions. The cervicovaginal microbiota plays a significant role in cervical cancer pathogenesis and represents a promising target for future diagnostic and therapeutic strategies. However, further research is required to better understand microbiota–host interactions and to develop effective microbiome-based interventions.